1996
DOI: 10.1007/bf01448373
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide study of developmental and gender prevalence for psychopathology in childhood and adolescence

Abstract: Psychopathology was assessed through standardized observations by teachers of 1,400 youths 5 through 17 years old comprising the national norm sample of the Adjustment Scales for Children and Adolescents. The sample was stratified according to the US. population by age, sex, ethnicity, parent education, family structure, national region, community size, and handicapping condition. The maladjusted portion of the sample for each of six specific syndromes was examined for departures from expected developmental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
2
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 39 publications
5
33
2
3
Order By: Relevance
“…Numerous studies have found that boys are more physically aggressive [McDermott, 1996;Tiet et al, 2001] and have a higher rate of CDs [Robins, 1991] than girls. Findings with regard to oppositional defiant disorder (ODD), often a precursor to CD [Lahey et al, 1992;Loeber et al, 2000], are less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that boys are more physically aggressive [McDermott, 1996;Tiet et al, 2001] and have a higher rate of CDs [Robins, 1991] than girls. Findings with regard to oppositional defiant disorder (ODD), often a precursor to CD [Lahey et al, 1992;Loeber et al, 2000], are less consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Gotovo sva istraživanja pokazala su kako stariji dječaci iskazuju više nasilnoga ponašanja (Olweus, 1998;Velki, 2012a). Dječaci su tjelesno i verbalno nasilniji (Espelage, Bosworth i Simon, 2000;McDermott, 1996), a novija istraživanja pokazuju da kada su u pitanju relacijski i indirektni oblici nasilja, dječaci su podjednako nasilni, ako ne i malo više nasilni, od djevojčica (Olwues, 2010). Dječaci su i češće žrtve svih oblika vršnjačkoga nasilja (Olweus, 1998(Olweus, , 2010.…”
Section: Uvodunclassified
“…Jedina razlika između ukupne i tjelesne vršnjačke viktimizacije javila se u prvom koraku regresijske analize, pri čemu se muški spol pokazao značajnim prediktorom tjelesne viktimizacije (iako u ostalim koracima i završnoj soluciji nije više bio značajan). Kako su dječaci češće uključeni u nasilno ponašanje (bilo kao žrtve ili nasilnici), posebice kada je u pitanju tjelesno vršnjačko nasilje koje se smatra djelomično normativnim ponašanjem dječa-ka, odnosno dijelom njihova odrastanja (Espelage i sur., 2000;McDermott, 1996;Olweus, 2010) dobiveni su rezultati očeki-vani.…”
Section: Vršnjačka Viktimizacijaunclassified
“…For instance, studies using rating scales and structured diagnostic interviews have shown that females have fewer externalizing problems, including conduct disorder, delinquency, and aggression (Bauermeister, 1992;deHaas & Young, 1984;Erne, 1992;McDermott, 1996), present with less disruptive behavior in classroom settings (deHaas, 1986), are at a lower risk for comorbid conduct disorder and oppositional defiant disorder (Biederman, et aI, 2002), display significantly less gross motor activity (James & Taylor, 1990), and have significantly lower rates of hyperactivity, aggression, conduct problems, impulsivity, inattention, distractibility, and oppositional defiance as compared to boys (Barkley, 1989;Bauermeister, 1992;Befera and Barkley, 1985;Berry, et aI., 1985;deHaas, 1986;deHaas & Young, 1984;Gaub & Carlson, 1997b;Newcom, et aI., 2001). …”
Section: Ad/hd and Externalizing Problemsmentioning
confidence: 99%
“…Although some studies have found no differences on measures of externalizing problems with males and females (Berry, et al, 1985;Biederman, et al, 1999;Breen & Altepeter, 1990;Brown, Madan-Swain, & Baldwin, 1991;Castellanos, et al, 2000;Hom, Wagner, & Ialongo, 1989;James & Taylor, 1990;Kashani, Chapel, Ellis, & Shekim, 1979;Sharp, et al, 1999;Silverthorn, Frick, Kuper, & Ott, 1996), the majority indicate that boys display more externalizing behaviors, such as aggression, hyperactivity, and conduct problems, than girls (Arcia and Conners, 1998;Arnold, 1996;Barkley, 1998;Bauermeister, 1992;Befera & Barkley, 1985;Berry, et al, 1985;Biederman, Newcom, et al, 1991;Bird, et al, 1993;Carlson, Tamm, & Gaub, 1997;deHaas & Young, 1984;Erne, 1992;Gaub & Carlson, 1997b;Gershon, 2002;Hartung, et al, 2002;Heptinstall & Taylor, 1996;Hinshaw, 2002;Leadbeater, Kupermine, Blatt, & Hertzog, 1999;Lewinsohn, et aI., 1993;Lumley, et aI., 2002;McDermott, 1996;Newcom, et aI., 2001;Waschbusch, 2002;Zahn-Waxler, 1993). The current results support the bulk of the research and demonstrated that on all parent and teacher ratings of externalizing behaviors, males showed significantly higher scores than females.…”
Section: Gendermentioning
confidence: 99%